PENGATURAN HUKUM TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL - Novianti; Sambas, Nandang (LPPM STIH Awang Long, 2025)
Legal regulation of defamation through social media is becoming an increasingly complex issue because it is carried out in a digital space that does not recognize territorial and time boundaries. The purpose of this study is to find out what are the legal regulations regarding criminal acts of defamation on social media based on Law Number 11 of 2008. The research method used is a normative research type because this study describes existing problems, to be further discussed with studies based on legal theories and then linked to applicable laws and regulations in legal practice. Article 27 Paragraph (3) of Law Number 11 of 2008 concerning the ITE Law states that anyone who intentionally and without the right distributes and / or transmits and / or makes accessible electronic information that contains insults and / or defamation. Criminal sanctions for violations of this article are regulated in Article a maximum of 4 (four) years imprisonment and / or a maximum fine of Rp. 750,000,000.00 (seven hundred and fifty million rupiah.”